2005
DOI: 10.1039/b417279p
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide mono(borohydride) complexes of diamide-diamine donor ligands: novel single site catalysts for the polymerisation of methyl methacrylate

Abstract: Samarium chloride and borohydride complexes of the diamide-diamine ligands (2-C5H4N)CH2N(CH2CH2NR)2(R = SiMe3 or mesityl) are described; the borohydride compounds are the first polydentate amide-supported single component lanthanide catalysts for the controlled polymerisation of polar monomers, and also represent the first lanthanide borohydride complex for the polymerisation of methyl methacrylate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 18 publications
3
46
0
Order By: Relevance
“…[15,17,19,20,37] Finally, diamide-diamine, guanidinate, and alkoxide monoborohydride complexes have recently been reported to initiate the polymerization of MMA with rather syndio-stereospecificity. [38][39][40] Results reported with Group 3 borohydride complexes remain rather limited. By using the tetradentate dianionic ligand (2-C 5 H 4 N)-CH 2 N(CH 2 CH 2 NSiMe 3 ) 2 (N 2 NN SiMe 3 ), Mountford and co-workers showed in preliminary studies that the monoborohydride complex [(N 2 NN SiMe 3 )SmA C H T U N G T R E N N U N G (BH 4 )] 2 afforded PMMA in 50 % yield with a slight syndiotactic tendency ( % 52 % rr; 15 % mm; 33 % mr), M n,exptl % 2.3M n,calcd , and M w /M n % 1.23.…”
Section: H T U N G T R E N N U N G (Bh 4 ) 3 -A C H T U N G T R E N Nmentioning
confidence: 95%
“…[15,17,19,20,37] Finally, diamide-diamine, guanidinate, and alkoxide monoborohydride complexes have recently been reported to initiate the polymerization of MMA with rather syndio-stereospecificity. [38][39][40] Results reported with Group 3 borohydride complexes remain rather limited. By using the tetradentate dianionic ligand (2-C 5 H 4 N)-CH 2 N(CH 2 CH 2 NSiMe 3 ) 2 (N 2 NN SiMe 3 ), Mountford and co-workers showed in preliminary studies that the monoborohydride complex [(N 2 NN SiMe 3 )SmA C H T U N G T R E N N U N G (BH 4 )] 2 afforded PMMA in 50 % yield with a slight syndiotactic tendency ( % 52 % rr; 15 % mm; 33 % mr), M n,exptl % 2.3M n,calcd , and M w /M n % 1.23.…”
Section: H T U N G T R E N N U N G (Bh 4 ) 3 -A C H T U N G T R E N Nmentioning
confidence: 95%
“…7 Since then, many rare a Department of Chemistry, University of York, Heslington, York, UK YO10 5DD b earth systems containing sterically-demanding ligands have been developed and studied for the controlled ROP of e-CL and lactide, including bis(phosphanyl)amide, 8 iminophenolato, 9 pyridyl amido, 10 pyridylmethyl indenyl, 11 bis(phenolate), 12 guanidino, 13 guanidinate, 14 or amine(phenolate), 15 and diamide-diamine ligands. 16 It has been shown through this extensive research that the behaviour of lanthanide complexes for the living ROP of e-CL can be tuned by altering the ancillary ligands attached to the metal centre. It has also been shown that the size of the central metal ion in these lanthanide based initiator systems also plays a crucial role in their design.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Note, however, that resonances diagnostic for the bis(phenolate) were not observed in the 1 H NMR spectra of the polymers prepared from 1 and 3, suggesting that the ligand did not act (or not significantly) as an initiating group in those polymerizations, in contrast to those mediated by 2 (vide infra).…”
mentioning
confidence: 80%
“…This offers an efficient approach to overcome some limitations of the cyclopentadienyl paradigm in tuning the metal atom coordination environment and eventually increasing the catalyst performance. 3 Thus, diamide-diamine, 4 diaminobis(phenoxide) 5 and guanidinate [6][7][8] ligands have allowed the synthesis of lanthanide borohydride complexes that have demonstrated high catalytic activity in controlled polymerizations of methyl methacrylate, 4,7,8 lactide 5,6 and e-caprolactone. 4,5 Linked dianionic bis(phenoxide) ancillary ligands containing backbones of different length, structure, donor atom sets and possessing various denticity have a number of advantages: they are usually easy to prepare, they often prevent ligand redistribution reactions, and provide the metal center with a rigid framework enabling stereospecific transformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation